Legal Review of Biodiversity Protection and Conservation of Biological Natural Resources in Indonesia - Donny Ferdiansyah; Toyib Zainal; Agustine Susi Mulyati; Majuri; Ibrahim Aji; Hardjito S. Darmojo (International Journal of Education, Vocational and Social Science, 2026)
This study examines the legal aspects of biodiversity (BD) protection and the conservation of biological natural resources in Indonesia. Using a normative–empirical legal research method, the study identifies substantial gaps between Law No. 5/1990 on Conservation of Biological Natural Resources and Their Ecosystems (KSDAHE) and the demands of contemporary conservation governance. Normatively, domestic regulations fail to adequately regulate Access and Benefit Sharing (ABS) and the protection of Traditional Knowledge (TK) of local communities, thereby creating vulnerabilities to biopiracy and distributive injustice. Empirically, criminal law enforcement against Illegal Wildlife Trade (IWT) remains ineffective due to lenient sentencing and difficulties in prosecuting organized crime networks, compounded by the limited use of preventive administrative instruments. The findings highlight the need for comprehensive legal reform focusing on integrating ABS and TK, strengthening criminal sanctions for biodiversity crimes, and harmonizing overlapping sectoral regulations. The overarching goal is to transform conservation law into an adaptive, equitable, and sustainability-oriented regulatory regime.